PEMINATAN KELUARGA BERENCANA (KB) PADA MASA PANDEMI COVID-19 DI PUSKESMAS 1 ULU - Lilis Susanti (Jurnal Kesehatan dan Pembangunan, 2022)
Introduction : Family Planning (KB) is a process that is realized by couples to decide the number and spacing of children and the time of birth to improve the welfare of mothers and children and control Indonesian population growth, especially during the Covid-19 Pandemic. Purpose: to describe the interest in family planning during the Covid-19 pandemic. Methods: This research uses a descriptive survey design, the sampling technigue uses a total sample. Namey 3367 active family planning participants. The data collection tool uses family planing. achievent decumentation. Results: the results of the study showed that active family planning participants during the Covid-19 pandemic experienced an increase in active family planning participants (0.55%), an increase in all types of contraceptives for active family planning participants, participants, namely the IUD decreased (1.12%), MOW (0.1 %) and those that experienced and increase were Implants increased (1.32%), New KB (Non MKJP) participants decreased, namely injections decreased (1.36%), Pills decreased (1.1%) and Condoms decreased 0.2%. And MOP remains 0%, no new participants added. when compared to the Target exceeds the target for Active KB participants and new KB participants are less than the target